THE FIRST 6TH-MONTH NUTRITIONAL STATUS OF A FULL-TERM CHILD IN EXCLUSIVE BREASTFEEDING: A LITERATURE REVIEW - Relisa Nuris Shifa; Sulistiawati; Endyka Erye Frety; Astika Gita Ningrum (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2021)
Background: The first six months after birth are part of the first 1000 days, a golden period for child development. In this period, the child needed proper nutrition to support optimal development and as nutrition programming. WHO recommends exclusive breastfeeding (EBF) for the first 6th-month. Adequacy of nutrition and optimal growth can be assessed using the nutritional status. Aim: This study analyzes the relationship between EBF for the first 6 months with the nutritional status of a full-term infant aged 0-6 months. The nutritional status assessed using anthropometric measurements and child growth standards. Methods: This type of literature review research uses the PRISMA, PICO, and Boolean Operator methods. The research question with PICO standard